An Accurate Facial Component Detection Using Gabor Filter - K. Sudhakar; P. Nithyanandam (Bulletin of Electrical Engineering and Informatics, 2017)
Face detection is a critical task to be resolved in a variety of applications. Since faces include various expressions it becomes a difficult task to detect the exact output. Face detection not only play a main role in personal identification but also in various fields which includes but not limited to image processing, pattern recognition, graphics and other application areas. The proposed system performs the face detection and facial components using Gabor filter. The results show accurate detection of facial components